Autophagic modulation by rosuvastatin prevents rotenone-induced neurotoxicity in an in vitro model of Parkinson's disease. (6th March 2017) - Kang, Seo Young; Lee, Sang-Bin; Kim, Hee Ju; Kim, Hee-Tae; Yang, Hyun Ok; Jang, Wooyoung
Highlights: Autophagy is seen as an important mechanism in Parkinson's disease pathogenesis. Rosuvastatin revealed neuroprotective properties via modulating autophagy. Rosuvastatin could be a new candidate for treating Parkinson's disease. Abstract: Statins have been reported to have neuroprotective effects through anti-oxidant, anti-apoptotic, and anti-inflammatory mechanisms, and statin can also modulate autophagic signaling in an oxygen-toxicity models. Therefore, we investigated the effects of statin on autophagy markers and evaluated the neuroprotective effect of rosuvastatin against rotenone-induced neurotoxicity. As an in vitro model of Parkinson's disease(PD) we adopted the rotenone-induced neurotoxicity model in SH-SY5Y cells. Cell viability was measured using the MTT assay, and to detect the expression of LC3 and α-synuclein, immunofluorescence analysis was performed. Intracellular signaling proteins associated with autophagy were explored via immunoblotting. Treatment with rosuvastatin alone increased the levels of mTOR-independent/upstream autophagy markers, including Beclin-1 and AMPK. Rotenone treatment of SH-SY5Y cells reduced their viability and α-synuclein expression; simultaneous exposure to rosuvastatin significantly restored these parameters. Rotenone enhanced mTOR expression and suppressed Beclin-1 expression, indicating suppression of the autophagic system. However, combined treatment with rosuvastatin also restored the Beclin-1 expression and decreased mTOR expression. We demonstrated the neuroprotective effect of statin in SH-SY5Y cells against rotenone-induced neurotoxicity, as well as the modulation of ɑ-synuclein expression. The neuroprotective mechanism is likely to be associated with enhanced autophagy. The neuroprotective effect of statin on rotenone-induced dopaminergic neurotoxicity with modulation of autophagy provides a new therapeutic strategy for the treatment of PD.